Dual threat of comorbidity of celiac disease and systemic lupus erythematosus. Issue 5 (May 2021) - Ma, Yimin; Zhuang, Duanming; Qiao, Zhenguo
Celiac disease (CD) is a chronic immune-mediated intestinal disease that is characterized by production of autoantibodies directed against the small intestine. The main clinical manifestations of CD are typically defined as those related to indigestion and malabsorption. These manifestations include unexplained diarrhea or constipation, abdominal pain, bloating, weight loss, anemia, failure-to-thrive in children, and decreased bone density. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by heterogeneous clinical manifestations, which may also involve the gastrointestinal tract. Comorbidity of CD and SLE is rare, and the overlapping symptoms and nonspecific clinical presentation may pose a diagnostic challenge to clinicians. We report here a case of SLE with CD, which mainly manifested as recurrent diarrhea, uncorrectable electrolyte disorders, and severe malnutrition. Through review, we hope to further improve our understanding and diagnostic level of this combination of diseases.